The scale insects (Hemiptera: Coccoidea) of economie importance in the Kazimierz Landscape Park in Poland (Bollettino di zoologia agraria e bachicoltura, 2024)
ies widely known as pests only Parthenolecanium comi (Bouché), P.pomeranicum (Kawecki), Aulacaspis rosae (Bouché ), Carulaspis juniperi(Bouché ), Lepidosaphes ulmi (L.) and Leucaspis pini (Hartig) are of greateconomie importance as they appeared with high frequency and high density, inthe Kazimierz Landscape Park. The species which are characterized by lowfrequency, but appearing on their hosts with high density are also of economiesignificance for trees and shrubs. These are: Kermes quercus (L.),Parthenolecanium rufulum (Cockerell), Asterodiaspis variolosa (Ratzeburg),Chionaspis salicis (L.) and Leucaspis loewi (Colvée). Attention should also bepaid to Planococcus vovae (Nassonov) which was characterized by relatively highfrequency, but occurred on the junipers only at low density. Another group ofscale insects was composed of the species which were characterized by lowfrequency and occurred on their hosts only at low density.
Keywords: Hemiptera; Coccoidea; economie importance; Poland